Effects of low molecular weight polysaccharide from Sargassum thunbergii against palmitic acid-induced intracellular lipid accumulation in 3T3-L1 adipocyte and HepG2 cells - Hyo-Geun Lee; D.P. Nagahawatta; M.J.M.S. Kurera; Kyung-Mo Song; Yun-Sang Choi; You-Jin Jeon; Min-Cheol Kang (Food Science and Human Wellness)
Low molecular weight polysaccharides can be isolated from Sargassum thunbergii (LMPST) and in vitro experiments were conducted to evaluate the inhibitory effects on lipids. Two natures of LMPST were attained from S. thunbergii and appraised their LMPST on palmitic acid (PA) induced lipid accretion in HepG2, and 3T3-L1 cells. LMPST treatment lessened lipid deposition and intracellular free fatty acid and triglyceride intensities in PA-treated above mentioned cells. The mechanistic study publicized that LMPST2 significantly suppressed adipogenesis and stimulated the PA-treated 3T3-L1 cells occupied in the lipolysis pathway. Furthermore, in PA-treated HepG2 cells, the free fatty acid oxidation was significantly increased by LMPST2. Given these constructive properties of LMPST2 from S. thunbergii, is a potential candidate for diminishing the intracellular lipids, and for a therapeutic agent in those conditions.